2012
DOI: 10.1186/1472-6882-12-242
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial, antimycobacterial and antibiofilm properties of Couroupita guianensis Aubl. fruit extract

Abstract: BackgroundCouroupita guianensis Aubl. (Lecythidaceae) is commonly called Ayahuma and the Cannonball tree. It is distributed in the tropical regions of northern South America and Southern Caribbean. It has several medicinal properties. It is used to treat hypertension, tumours, pain, inflammatory processes, cold, stomach ache, skin diseases, malaria, wounds and toothache.MethodsThe fruits of Couroupita guianensis were extracted with chloroform. Antimicrobial, antimycobacterial and antibiofilm forming activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…In a similar study, chloroform fruit extract displayed moderate activity against gram-positive bacteria, B. subtilis (14 mm), Micrococcus luteus (18 mm), Enterobacter aerogenes(19 mm) and Staphylococcus aureus (26 mm), gram-negative bacteria Shigella flexneri (20 mm), Klebsiella pneumonia (18 mm), P. aeruginosa(8 mm) and Proteus vulgaris (12 mm). Further, the same extract showed 52% antibiofilm activity against P. aeruginosa at 2 mg/mL BIC, thereby demonstrating its ability to complex with the bacterial cell wall(47). In another study the ethanol fruit rind extract (at 10 mg/mL) showed moderate activity against S. aureus, E. coli, C. diphtheriae and Micrococcus sp (34)…”
mentioning
confidence: 95%
“…In a similar study, chloroform fruit extract displayed moderate activity against gram-positive bacteria, B. subtilis (14 mm), Micrococcus luteus (18 mm), Enterobacter aerogenes(19 mm) and Staphylococcus aureus (26 mm), gram-negative bacteria Shigella flexneri (20 mm), Klebsiella pneumonia (18 mm), P. aeruginosa(8 mm) and Proteus vulgaris (12 mm). Further, the same extract showed 52% antibiofilm activity against P. aeruginosa at 2 mg/mL BIC, thereby demonstrating its ability to complex with the bacterial cell wall(47). In another study the ethanol fruit rind extract (at 10 mg/mL) showed moderate activity against S. aureus, E. coli, C. diphtheriae and Micrococcus sp (34)…”
mentioning
confidence: 95%
“…The tree possesses antibiotic, anti-inflammatory, antifungal, antiseptic, antipyretic and analgesic properties. 16 theamazonian natives are also known to use infusions obtained from the flower, bark and leaves of the cannonball tree to treat hypertension, tumours and pain. 17 the leaves of the CG are used specifically for the treatment of the skin diseases, toothache, wound healing and malaria.…”
Section: Identification Of the Plant Samplesmentioning
confidence: 99%
“…The antibacterial activity of herbal plants is may be due to adsorption of polyphenols to bacterial membranes with disruption of the membrane and subsequent leakage of cellular contents. In this study, ethanolic A. Occidentale leaves contains the phenolic active compound, such as anacardic acid which shows antimicrobial effect [17][18][19][20][21]. Flavonoids have been recognised as having a protective effect in plants against microbial invasion by plant pathogens.…”
Section: In Vitro Antibacterial Activity Of Ethanolic Extracts Of Plantsmentioning
confidence: 99%